TRAUMATOGENIC FEELINGS: A STUDY OF LITERARY AND CINEMATIC REPRESENTATIONS IN SELECT WORKS - Joy, Heavenly; K., Balakrishnan (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The creative expressions of traumas can be literary works, blogs, films or documentaries. Such works do serve in expurgating the traumatogenic feelings in given situations almost in a cathartic manner. This paper aims to analyze the representations of trauma in select works-novels adapted into films. It tries to bring out the significance of educating people about trauma with the help of literary and cinematic depictions. Critics like Anne Whitehead and Michael Rothberg have studied various representations of trauma. However, this paper considers the role of media in informing people of probable traumatic situations. A close reading of literary and cinematic representations of trauma in The Secret Life of Bees, and We Need to Talk about Kevin is attempted here to understand the impact of traumatogenic feelings in individuals caught in convulsive situations. The Secret Life of Bees (2008) by Gina Prince-Bythewood is an adaptation of Sue Monk Kidd’s novel of the same title. It presents the story of Lily Owens, who has lost her mother at the tender age of four. She stays with her abusive father T Ray and their servant Rosaleen. Her life is engulfed with many unfavourable conditions, which she battles along with Rosaleen. We Need to Talk about Kevin (2011) is the filmic adaptation of Lionel Shriver’s novel of the same name. It narrates the story of Kevin who murders his father and sister. The selected representations will show how children are vulnerable to traumas, as a shaping factor in their conduct and behaviour- thus giving the analysis a psychoanalytic touch-which bears on the cultural consequences of traumatic experiences.